Congenital X-Linked Autophagic Vacuolar Myopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A Chinese-American family with a severe X-linked congenital autophagic vacuolar myopathy (AVM) affecting 7 boys is reported from the National Center of Neurology and Psychiatry, Kodaira, Tokyo, and Utano National Hospital, Kyoto, Japan; and Shandong University, Jinan, China.